2020
DOI: 10.4300/jgme-d-19-00782.1
|View full text |Cite
|
Sign up to set email alerts
|

Are USMLE Scores Valid Measures for Chief Resident Selection?

Abstract: Background The US Medical Licensing Examination (USMLE) Step 1 and Step 2 scores are often used to inform a variety of secondary medical career decisions, such as residency selection, despite the lack of validity evidence supporting their use in these contexts. Objective We compared USMLE scores between non–chief residents (non-CRs) and chief residents (CRs), selected based on performance during training, at a US academic medical center that sponsors a variety of graduate medical education programs. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…2 Research from other clinical specialties also has suggested that commonly used metrics (such as USMLE scores and interview performance) are not strongly predictive of residency success. [28][29][30] These findings may also reflect the challenges of using the ACGME Milestones as an assessment tool. These Milestones, while reflecting the theoretical educational outcomes of a program, may also be an imperfect measure of resident performance in the real world.…”
Section: Discussionmentioning
confidence: 85%
“…2 Research from other clinical specialties also has suggested that commonly used metrics (such as USMLE scores and interview performance) are not strongly predictive of residency success. [28][29][30] These findings may also reflect the challenges of using the ACGME Milestones as an assessment tool. These Milestones, while reflecting the theoretical educational outcomes of a program, may also be an imperfect measure of resident performance in the real world.…”
Section: Discussionmentioning
confidence: 85%
“…Twenty-five studies were unable to be pooled. 59–83 Most of these studies could not be pooled because they did not analyze a continuous Step 2 CK score or their outcome of interest was not examined by at least 2 other studies. Of these studies, 2 showed a mixed relationship between higher Step 2 CK scores and the desired outcome, 5 showed a statistically unremarkable relationship between a higher Step 2 CK score and the desired outcome, and 18 showed a statistically significant relationship between a higher Step 2 CK score and the desired outcome.…”
Section: Resultsmentioning
confidence: 99%
“…For full-text review, 82 articles were reviewed for inclusion and 14 were excluded, leaving 68 studies that met inclusion criteria. 16–83 Agreement on study inclusion achieved a κ value of 0.85.…”
Section: Resultsmentioning
confidence: 99%
“…For example, overemphasis on minor differences on scholastic aptitude test scores and advantages given to “legacy” applicants may lead to a less diverse undergraduate cohort. 41 Notwithstanding the lack of evidence that clinical competence is linearly correlated with a United States Medical Licensing Examination (USMLE) score, 42 residency programs in anesthesiology and other specialties have placed a greater premium on USMLE scores than other factors such as commitment to the community, demonstrated passion for practicing medicine, or research interests. 43 An observational study suggests a range of USMLE scores compatible with passing the anesthesiology basic staged examination.…”
Section: Barriers To Diversity: Defining the Challenges In Diversity ...mentioning
confidence: 99%